A bibliometric and visualization-based analysis of temozolomide research hotspots and frontier evolution - Song, Peng; Li, Hui; Xu, Kuo; Li, Zi-Wei; Ren, Xia; Fu, Xian-Jun (Frontiers in Oncology, 2022)
The literature related to TMZ research in the Web of Science (WOS) database was analyzed using bibliometrics and visualization by Citespace and VOSviewer.The publication status (number of publications, institutions, and frequency of citations), collaborations, and research focus was analyzed to clarify the current situation of TMZ research. And the recent research on TMZ provides a detailed summary. Based on objective data analysis, this study provides a complete analysis portraying the progression of historical milestones in TMZ development and future research directions from various TMZ research domains.